Геодинамическое развитие структур Украины - Дерябин, Н.И. (Видавничий дім "Академперіодика" НАН України, 2007)
In the development history of the Ukrainian geological structures, nine tectonic cycles including their riftogenous, contractional, and platform stages are recognized.